1995
DOI: 10.1080/02841859509173372
|View full text |Cite
|
Sign up to set email alerts
|

Fine Needle Aspiration Biopsy of Hydatid Cysts

Abstract: Fine needle aspiration biopsy (FNAB) was performed in 31 patients with hydatid disease by 15 operators in 41 biopsy events during the period 1983-93. The FNABs were unintentionally done without prior clinical suspicion of hydatid cysts (HCs) in 18 patients and intentionally (with prior clinical suspicion of HC) in 13 patients for pathologic confirmation required for specific therapy. The FNABs were performed with the guidance of fluoroscopy (n=7), CT (n= 14) or ultrasonography (n= 10). The material included bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The multilocular lesion with several daughter cysts inside the mother cyst is characteristic, but not pathognomonic of hydatid disease (Martin et al 1993, Essadki et al 1996. Endovesicular daughter cysts, present in most of our cases, are regarded as unusual in musculoskeletal cystic echinococcosis by some authors (Von Sinner et al 1995, Guthrie et al 1996, Merkle et al 1997. MR images were obtained in 4 of our patients before diagnosis, and were highly suggestive of hydatid disease.…”
Section: Discussionmentioning
confidence: 99%
“…The multilocular lesion with several daughter cysts inside the mother cyst is characteristic, but not pathognomonic of hydatid disease (Martin et al 1993, Essadki et al 1996. Endovesicular daughter cysts, present in most of our cases, are regarded as unusual in musculoskeletal cystic echinococcosis by some authors (Von Sinner et al 1995, Guthrie et al 1996, Merkle et al 1997. MR images were obtained in 4 of our patients before diagnosis, and were highly suggestive of hydatid disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, percutaneous aspiration of hydatid cysts was believed to be contraindicated because of the risk of anaphylaxis and spillage of scolices, resulting in peritoneal seeding and dissemination (2,5,8,17,18). Von Sinner et al (22) suggested the use of fine needle aspiration biopsy to evaluate suspected hydatid cysts having nonspecific signs in medical imaging and negative serology. Salama et al (23) reported the use of percutaneous cyst puncture followed by in-stillation of hypertonic saline in the treatment of 45 patients with hepatic hydatid disease.…”
Section: Discussionmentioning
confidence: 99%
“…The authors advocate that with adequate prophylaxis against anaphylaxis and dissemination, CT guided aspiration of spinal hydatid cysts with hypertonic saline irrigation and subsequent chemotherapy may be an alternative to surgical therapy in selected cases. 39,41 Other minimally invasive techniques such as endoscopic evacuation of cyst material has been reported in the literature. 31 We think that minimally invasive methods may be of value in selected patients with localized spinal disease, in whom surgical therapy is contraindicated.…”
Section: Minimally Invasive Techniquesmentioning
confidence: 99%
“…39,41 This technique however is usually avoided in spinal disease due to the risk of cyst rupture and severe anaphylaxis. 13 In the single reported case, Spektor et al 41 described the successful decompression of an extradural cervical spinal hydatid cyst by CT guided ®ne needle aspiration with complete resolution of quadriplegia.…”
Section: Minimally Invasive Techniquesmentioning
confidence: 99%
See 1 more Smart Citation